‘Medical Apology’ at crossroads: An effective dispute resolution mechanism versus admission of liability - Jahn Kassim, Puteri Nemie; Mohamed, Duryana; Saleh, Muhammad Ridhwan (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
Apology has always been viewed as an important social conduct that is able to provide closure to a conflict situation. The aftermath of disputes and conflicts is usually fuelled with feelings of anger, injustice, mistrust and a tendency to sue. By making apologies which may include statements of regret and empathy, acceptance of responsibility as well as proper explanation of the events leading to the mishap, the severity of the aftermath situations can be significantly reduced. Further, studies have shown that proper apologising at this juncture can also be an effective dispute resolution mechanism that heals and preserves relationships as well as triggering settlement negotiations. However, medical practitioners are rather hesitant to apologise after the occurrence of adverse events fearing that this may be treated as an ‘admission of guilt’ and any statements made at this point may be admissible in judicial proceedings as evidence of fault or liability. Such implication occurred in the case of Gurmit Kaur A/P Jaswant Singh v Tung Shin Hospital & Anor [2013] 1 CLJ 699 HC in which the medical practitioner was found liable for negligence based on the apology given by him during the post-surgery consultation with his patient. Nevertheless, in recognition of the immense benefits of apology as an effective dispute resolution mechanism, several jurisdictions around the globe have developed ‘Apology Laws’ to explicitly preclude apologies made after adverse events as being treated as admission of fault or as evidence to prove liability. This paper seeks to discuss the function and effectiveness of apology in resolving medical disputes against the negative implications it has in the law of evidence. The paper will also provide recommendations for the enactment of ‘Apology Laws’ in Malaysia based on the experiences of selected countries in preserving the effectiveness of apologies within the parameters of a protective legislation.